GAMBARAN GANGGUAN MUSKULOSKELETAL PADA AREABAHU PADA GURU DI DAERAHJABODETABEK - Haura Balqis Subagio (2021)
Shoulder pain has always been the highest prevalence of the many musculoskeletal disorders that occur.. There are many factors that can affect pain in the shoulder area, both from internally and externally. When Covid-19 entered Indonesia, the goverment carried out Learning From Home in the field of education, where teachers interacted bravel. This can increase musculoskeletal disorders in teachers, especially in the shoulder area. This study aims to describe and examine data related to musculoskeletal disorders in the shoulder area in Jabodetabek teachers. The method used in this research is descriptive quantitative with a cross-sectional approach. The research sample was taken using the Krecjie and Morgan technique using the inclusion exclusion criteria so as to get a sample of 325 people. NMQ (Nordic Musculoskeletal Questionnaire) and NRS (Numeric Rating Scale) were used as parameters. Based on the results of the study, 150 people experienced shoulder complaints with the majority being 36-50 years old (39.1%), female (77%), and normal body proportions (29%). The conclusion of this study is to reduce complaints of shoulder pain with internal and external factors that can cause shoulder pain.